APPLICATION OF IMAGE OBJECTS USING JAVA ISLAND TOUR IN MICROSOFT VISUAL BASIC 6.0 - Raden Reza Adi Permono; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2003)
One who makes an interesting tourist attraction is about what's special aboutattractions. And the information is sometimes very difficult to obtain. So with thisapplication is expected to get a picture of these attractions, though have never visited.In this application, the author tries to provide information which supports about theseattractions. This application presents six fruit attractions on the island of Java, eachobject is given a picture tour with caption.